Microeconomía de la pobreza: el caso del Perú - Rivera, Iván (2012)
Poverty Microeconomics: The Peruvian caseThe microeconomic analysis of poverty in Peru shows the following results. First, poverty is mainly explained by the income of the poor which is not only low, but also highly unstable. Second, poverty is related to the poor’s bad decision making due to incomplete information, intertemporal inconsistency and or lack of self control, mainly in the saving, borrowing, preventive health, fertility and education decisions. Third, poverty depends of the external constraints the poor face in some markets where they are marginalized from automatic decision making, in health insurance, pensions, vaccines, water and sanitation. Fourth, the poor face more and bigger risks than the rest of the population. They have higher probability to fall in poverty traps than higher income groups, because their income is low and unstable and they lack thefinancial and institutional backing to buffer income fluctuations. Fifth, to combat poverty we have to modulate the poor’s decision through information diffusion and the use of mechanisms of behavioral economics such as framing and nudging decisions in health, education, insurance, pensions, etc. to induce good decision making and avoid procrastination. To improve the quality of education, health, nutrition services and social services we have to empower the users as well as strengthen the accountability of the providers. Private sector participation in the provision of social services should be promoted. The promotion of formal firms in the regions of extreme poverty, such as mining firms and related activities has shown proven results as a mechanism of rising and stabilizing the incomes of the poor.